The Mission's Children Practices of Appropriation in the Photographs of Marind Children in the Annalen van O.L. Vrouw van het H. Hart, 1907-1935 - Reichgelt, Marleen (2018)
The significance of children as instruments of socio-political change in colonial contexts is acknowledged in international research, but much remains unknown about the ways in which children were addressed and engaged in 'civilizing' practices. This article contributes to a better understanding of the involvement of local children in missionary 'civilizing' projects through the analysis of the visual representation of the children. More specifically, the photographs depicting Marind children from Dutch New Guinea in the most important periodical of the Missionaries of the Sacred Heart, the Annalen van O.L. Vrouw van het H. Hart, are analyzed with the help of a database containing 1300 photographs of the mission. The pictures give valuable insight in the strategies involved with the recruitment of children in the missionary project. The children were increasingly set apart from their parents and kin. This was done by removing them from their villages, providing them with missionary father figures, teaching them to work, instructing them in the Catholic faith, and dressing them in Western clothing. The selection and use of the photographs in the periodical elucidate how the 'civilizing' project was effectively a project of removal. The photographical narrative was part of a larger, multi-faceted system in which local children were appropriated by the mission.
Keywords: Catholic Church; Devotion to the Sacred Heart of Jesus; Marind (Indonesian people); Missionaries; Photography of children